Muscle Evaluation in Axial Spondyloarthritis—The Evidence for Sarcopenia - Valido, Ana; Crespo, Carolina Lage; Pimentel-Santos, Fernando M. (Frontiers in Medicine, 2019)
Sarcopenia is a syndrome defined as a progressive and generalized skeletal muscle disorder associated with an increased likelihood of adverse outcomes such as falls, fractures, physical disability, and death. The actual definition of sarcopenia is based on a reduction in the values of three parameters: strength, muscle mass quantity or quality, and physical performance (the determinant of severity). Muscle wasting is a common feature in several chronic diseases, such as spondyloarthritis (SpA), and significantly increases patient morbidity and mortality. Although there has been huge progress in this field over recent years, the absence of a clear definition and clear diagnostic criteria of sarcopenia has resulted in inconsistent information regarding muscle-involvement in SpA. Thus, the aim of this review is to collect relevant evidence on muscular changes occurring during the disease process from the published literature, according to the recommended tools for sarcopenia evaluation proposed by the European Working Group on Sarcopenia in Older People 2 (EWGSOP2). In addition, data from histological, electromyography, and biochemical muscle analyses of SpA patients are also reviewed. Overall, a reduction in muscle strength with a systemic decrease in lean mass seems to be associated with a gait speed compromise. This information is usually fragmented, with no studies considering the three parameters together. This paper represents a call-to-action for the design of new studies in the future.